The Integration of Artificial Intelligence in Islamic Religious Education Opportunities Challenges and Ethical Implications - Ahmed Hossein (https://ejournal.insuriponorogo.ac.id/, 2026)
The rapid advancement of Artificial Intelligence (AI) has transformed educational practices across various disciplines, including religious education. In Islamic Religious Education (IRE), AI technologies offer innovative opportunities to enhance learning effectiveness, personalize instruction, and improve access to educational resources. However, the integration of AI into Islamic education also presents pedagogical, ethical, and theological challenges that require critical examination. This study aims to explore the opportunities, challenges, and ethical implications of integrating Artificial Intelligence into Islamic Religious Education. Employing a qualitative library research approach, the study analyzes scholarly literature, educational policies, and contemporary discussions concerning AI in education and Islamic pedagogy. The findings indicate that AI can contribute positively to Islamic Religious Education by supporting adaptive learning, interactive instruction, digital accessibility, and student engagement. AI-powered tools such as intelligent tutoring systems, automated feedback applications, and conversational platforms may facilitate deeper understanding of Islamic teachings and improve learning outcomes. Nevertheless, concerns regarding the authenticity of religious content, academic integrity, data privacy, algorithmic bias, and excessive dependence on technology remain significant challenges. Ethical considerations are particularly important because Islamic education emphasizes moral development, spiritual values, and responsible human interaction. The study concludes that the successful integration of Artificial Intelligence in Islamic Religious Education requires balanced pedagogical strategies, ethical digital governance, teacher supervision, and contextualized implementation aligned with Islamic educational values. Artificial Intelligence should therefore function as a supportive educational instrument rather than a replacement for human educators and moral guidance.